1970
DOI: 10.1021/ma60014a002
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Anionic Polystyrenes. II. Dynamic Viscoelasticity of Blends of Narrow-Distribution Polystyrenes

Abstract: The dynamic viscoelastic properties of broad-distribution polystyrene and blends of narrowdistribution polystyrenes have been measured in the molten state. A comparison of the frequency dependences of the storage shear modulus G', loss modulus G", and relaxation spectrum H(7) of the blends and the broaddistribution polymer with those of the narrow-distribution polymers reveals that the effect of molecular weight distribution is very marked in the terminal and rubbery zones. The log G' us. log w curve for a bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(84 citation statements)
references
References 1 publication
11
73
0
Order By: Relevance
“…CAPTIONS OF THE FiGURE S (19) for pure polystyrene components and blends , al l of which fall on the same straight line wi th a slope of 3.7.…”
Section: 2 5 )mentioning
confidence: 93%
“…CAPTIONS OF THE FiGURE S (19) for pure polystyrene components and blends , al l of which fall on the same straight line wi th a slope of 3.7.…”
Section: 2 5 )mentioning
confidence: 93%
“…Using a right handed coordinate system to define the flow, the usual convention is retained with: 1 -the flow direction; 2 -the direction of the flow gradient, and 3 -the neutral direction. If a particle in simple shear flow is given coordinates (5i.S2'53) ^^ some time time tj previous to the present time t then the present coordinate position (xj,X2,X3) reads: Xj = Si + q(t -ti) 52 (1.1-2) X2 = Zz (1.1.3) X3 -£3 (1.1.4) 1 where q is the shear rate and the macroscopic deformation is s " q(t -tj). Also present in simple shear flow is a shear stress Pi2.…”
Section: Preamblementioning
confidence: 99%
“…4 The calculated values of G~N and JiN and also of Me are shown in Table VI. The value of J~N for the bulk PMMA 715, 2.15xl0-7 cm 2 / dyne, is consistent with the result reported in our previous paper, 5 which showed that the J~N was slightly dependent upon the molecular weight.…”
Section: Viscoelastic Properties In the Rubbery Zonementioning
confidence: 99%